PENGUATAN PERAN KOMITE SEKOLAH DALAM MENINGKATKAN KOMUNIKASI EFEKTIF ANTARA ORANG TUA SISWA DENGAN PIHAK SEKOLAH - Ridwan, Ridwan; Hasyim, Baso; Mahmud, Hilal; Muhaemin, Muhaemin (Kelola: Journal of Islamic Education Management, 2023)
This study aims to analyze and describe the role of the school committee in increasing effective communication between parents of students and the school at SMP Negeri 1 Lamasi, providing support, as a controller and as a mediator, in increasing communication between parents and the school regarding education. The role of the school committee can be in the form of assistance such as voluntary donations to improve learning and learning infrastructure facilities for students and provide consideration between parents and schools. Research data were collected using in-depth interview techniques, observation, and documentation studies with the following informants: school committee, principal, teachers, parents of students of SMP Negeri 1 Lamasi. Based on the results of research in the field, it shows that the role of this committee is not sufficient enough in carrying out its prominent role, namely as a giver of consideration, support, controller as well as a good mediator and liaison for the school and students' parents, thus the role of the committee in SMP Negeri 1 Lamasi school needs to be improve effective communication between parents of students and the school in this case in order to achieve a comfortable school for the school, parents of students and students in learning and learning activities.